2014
DOI: 10.1093/nar/gku646
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tRNA levels on decoding times of mRNA codons

Abstract: The possible effect of transfer ribonucleic acid (tRNA) concentrations on codons decoding time is a fundamental biomedical research question; however, due to a large number of variables affecting this process and the non-direct relation between them, a conclusive answer to this question has eluded so far researchers in the field. In this study, we perform a novel analysis of the ribosome profiling data of four organisms which enables ranking the decoding times of different codons while filtering translational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
281
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(295 citation statements)
references
References 75 publications
(168 reference statements)
5
281
0
Order By: Relevance
“…After processing and reverse-transcription, these are sequenced, mapped, and used to derive ribosomal density profiles. In order to estimate the typical nominal relative codon decoding times in endogenous S. cerevisiae genes under natural conditions, we implemented a novel statistical approach that filters biases and considers ribosomal traffic jams 20 These findings may suggest that in S. cerevisiae the effect of codon usage at the very beginning of the ORF is strongly related to mRNA folding via its effect on initiation (as suggested in prokaryotes 11,13,14 ), but it is also significantly related to elongation rates. Moreover, the results may also suggest that the decoding times of codons is different at the beginning of the ORF than afterwards 39 .…”
Section: Correlation Of Protein Levels With Mean Codon Decoding Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…After processing and reverse-transcription, these are sequenced, mapped, and used to derive ribosomal density profiles. In order to estimate the typical nominal relative codon decoding times in endogenous S. cerevisiae genes under natural conditions, we implemented a novel statistical approach that filters biases and considers ribosomal traffic jams 20 These findings may suggest that in S. cerevisiae the effect of codon usage at the very beginning of the ORF is strongly related to mRNA folding via its effect on initiation (as suggested in prokaryotes 11,13,14 ), but it is also significantly related to elongation rates. Moreover, the results may also suggest that the decoding times of codons is different at the beginning of the ORF than afterwards 39 .…”
Section: Correlation Of Protein Levels With Mean Codon Decoding Timesmentioning
confidence: 99%
“…Downloaded by [University of Nebraska, Lincoln] at 04: 45 26 August 2015 For example, it was suggested that in E. coli the folding strength of the mRNA near the START codon affects the translation initiation rate (and thus the protein levels), as it is related to the efficiency with which the pre-initiation complex recognizes the start codon 11,13 ; however, most of the open questions in the field remain unanswered due to the fact that almost all previous studies focused on the analysis of endogenous genes and on indirect measures of translation; and due to the fact that the answers to these questions may be condition-and organism-dependent 16 The ribosome elongation speed and its association with expression regulation is also not fully understood: some studies suggested that it is constant 18,19 , while others suggested that different codons have different decoding times, for example due to different tRNA levels 11,17,[20][21][22] . Other important questions relate to the effect of codon and nucleotide composition in different parts of the transcript on protein levels: while some studies proposed that the codon distribution in all parts of the ORF, and specifically in those related to translation elongation, can affect the protein abundance 1,17,23 , others claimed that only the nucleotide composition near the beginning of the ORF impacts protein levels 11 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, ribosome profiling 20 holds out the promise that it may be possible to directly measure the k A,i values for a transcript [21][22][23][24] . In such a situation, assumption A4 is not necessary.…”
Section: A5mentioning
confidence: 99%
“…Individual codon translation rates in CHO cells, however, have not been measured. There have been at least five different estimates of codon translation rates in other organisms extracted from ribosome profiling data [21][22][23] or calculated from theory 24 . These estimated codon translation rates do not correlate with each other, even when calculated for the same organism ( Supplementary Fig.…”
Section: A5mentioning
confidence: 99%
“…It has been pointed out that GC-rich genomes prefer G or C in the 5 anticodon positions in their tRNA sets. The level of various intracellular tRNAs in turn influences mRNA decoding efficiency, which could directly result in the expression barrier of a rare codoncontaining gene [17,18]. Previously, several plasmid-based systems for supplementation of rare tRNAs have been developed to overcome codon bias in E. coli and Streptococcus gordonii [19][20][21].…”
Section: Introductionmentioning
confidence: 99%